Astrocyte: A Foe or a Friend in Intellectual Disability-Related Diseases - Wang, Busong; Zou, Lu; Li, Min; Zhou, Liang (Frontiers in Synaptic Neuroscience, 2022)
Intellectual disabilities are a type of neurodevelopmental disease caused by neurological dysfunction. Their incidence is largely associated with neural development. Astrocytes are the most widely distributed cells in the mammalian brain. Previous studies have reported that astrocytes only supported and separated the neurons in the brain. However, recent studies have found that they also play an important role in neural development. Understanding the astrocyte mechanism in intellectual development disorder-related diseases will help provide new therapeutic targets for the treatment of intellectual disability-related diseases. This mini-review introduced the association between astrocyte and intellectual disabilities. Furthermore, recent advances in genetic and environmental factors causing intellectual disability and different pharmaceutical effects of intellectual disability-related drugs on astrocyte have been summarised. Finally, we discussed future perspectives of astrocyte-based therapy for intellectual disability.